Error Analysis Found in Students’ Writing Composition in Simple Past Tense of Recount Text - Fitria, Tira Nur (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study was to find the types of error analysis and the most dominant form of error analysis found in the Simple Past Tense Writing Composition of Students, especially in Recount Text. This study used a mixed-method both qualitative and quantitative approach. From the study, it was shown that the error of the students in writing Simple Past Tense composition consists of certain elements of writing, such as grammar, punctuation, and spelling. There were 57 data in grammar, or 53.37 %, consisting of errors in class terms like in determiner/article (25 data or 43.86 %), in verb (14 data or 24.56 %), in a preposition (11 data or 19.30 %) and the last in a noun (7 data or 12.28 %). While the most dominant error was in determiner/article. Second, in the aspect of spelling, there were 26 data or 21.70 %). Third, in the aspect of punctuation, there were (23 data or 24.53 %). It is shown that the most dominant error found in the students’ writing composition in the grammar aspect is 57 data or 53.37 percent based on the frequency of each aspect of error.